2015
DOI: 10.1136/bcr-2015-209325
|View full text |Cite
|
Sign up to set email alerts
|

Acute necrotising pancreatitis derived from low-dose corticosteroid use: an important reminder of clinical management

Abstract: Although the exact mechanism is unknown, incidence of drug-induced pancreatitis from corticosteroids is well established in the medical literature. Commonly reported in chronic steroid-dependent individuals who require large doses for a wide array of pathologies, the incidence of damage to the pancreas from low-doses have not been well described. We report a case of a 68-year-old woman who presented with severe abdominal pain, nausea and vomiting, 3 days after the initiation of low-dose methylprednisolone for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Our patient took metoprolol for three years without adverse events and during her entire hospitalization, including the time of pancreatic enzyme level normalization and symptomatic improvement. Few cases reported pantoprazole [46,47] and methylprednisolone [48][49][50][51][52][53][54] induced AP, but in our patient, these drugs were continued throughout the hospital stay as well. Parallel to the rechallenge, our patient's diet was advanced, which could cause recurrence of AP.…”
Section: Discussionmentioning
confidence: 59%
“…Our patient took metoprolol for three years without adverse events and during her entire hospitalization, including the time of pancreatic enzyme level normalization and symptomatic improvement. Few cases reported pantoprazole [46,47] and methylprednisolone [48][49][50][51][52][53][54] induced AP, but in our patient, these drugs were continued throughout the hospital stay as well. Parallel to the rechallenge, our patient's diet was advanced, which could cause recurrence of AP.…”
Section: Discussionmentioning
confidence: 59%
“…Whether the present case or the intra-articular injection case share a cause-and-effect relationship between the steroids and the pancreatitis is only speculative, but some elements are clear. First, glucocorticoids, even in small doses, are a commonly known risk factor for pancreatitis [9,13]. Second, the literature shows the risk for development of pancreatitis after taking oral steroids is highest 4-14 days after the medication is taken [13].…”
Section: Discussionmentioning
confidence: 99%
“…Less than 5% of cases are secondary to drug-induced adverse effects [8]. Pancreatitis has been reported to be associated with steroid medication use, even in cases in which the steroid dosages would be considered too low to suppress the HPA axis [9]. Here, we report a case of transient glucocorticoid-induced pancreatitis that occurred 1 week after lumbar epidural steroid injection.…”
Section: Introductionmentioning
confidence: 86%
“…Whether subgroups exist and how they should possibly influence recommendations on the dosage, treatment initiation and duration needs further investigation. When considering corticosteroid dosage and treatment duration, practitioners should keep in mind that studies have found evidence of corticosteroids causing or increasing the risk of acute pancreatitis [ 21 , 22 ].…”
Section: Limitationsmentioning
confidence: 99%
“…Corticosteroids are generally contraindicated because of the risk of gastric ulcerations and reduced reticuloendothelial activity [ 19 ]. Recent human case studies have indicated that corticosteroids may even induce acute pancreatitis [ 21 , 22 ]. In dogs with hyperadrenocorticism, one study reported increases in canine pancreatic-specific lipase (Spec-cPL) concentrations without any obvious clinical evidence of pancreatitis [ 23 ].…”
Section: Introductionmentioning
confidence: 99%